Integrating Artificial Intelligence and Medical Chatbots into Medical Education: Insights from Medical Students - Upadhayay, Namrata (Medical Journal of Eastern Nepal, 2025)
BackgroundThe growing technology landscape in the Artificial Intelligence (AI) era requires continuous curriculum advancement. We aimed to explore medical students knowledge, attitudes and perceptions of integrating AI and chatbots into the curriculum.Method A cross-sectional questionnaire-based study conducted among pre-clinical students. Of 150 students, 131 responded. The questionnaire assessed their knowledge, attitude and perception toward AI and chatbots use in the medical curriculum. After thematic analysis, data are expressed as percentage.ResultsStudents showed a moderate knowledge (73.91%) and a predominantly negative attitude (84.56%) toward integrating AI into curriculum. Concerns included data privacy, trust issues, self-harm (illegal practices), creativity loss, questionable accuracy and reliability, limits skill development, overdependence, errors and liabilities, and lack of ethical judgment. Most (71.76%) had never practiced medical-specific chatbots aligning with their negative attitude. The identified barriers were limited accessibility, inadequate training and guidance. Students showed mixed responses about AI in clinical purposes: diagnosis, telemedicine, and virtual patient simulations. Students commonly used AI tools were non-medical, low-risk applications.ConclusionStudents knowledge of AI is still developing and attitudes were predominantly negative or cautious toward its integration into the curriculum. Before implementation, concerns regarding ethics, training, and access must be addressed. Students have strong digital familiarity outside of academic and health contexts. These findings suggest the need for carefully regulated, context-specific integration of AI in medical education, with a focus on building capacity, addressing ethical concerns, and ensuring equitable access.